1999
DOI: 10.1007/s11938-999-0022-5
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholic liver disease

Abstract: The traditional approach to alcoholism is treatment of underlying psychological and behavioral problems. Earlier and more direct avenues to prevent or counteract alcohol's effects include a focus on early detection of alcoholism, using, in part, biochemical markers of heavy drinking such as carbohydrate-deficient transferrin (CDT) and screening, among heavy users of alcohol, for signs of medical complications. Only a few heavy drinkers eventually develop liver cirrhosis. Because no practical genetic markers ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…S-Adenosylmethionine, polyenylphosphatidylcholine, betaine, and antioxidants like vitamins A, C, E, B6, and B12 as well as branched chain amino acids are examples of substances studied for their potential efficacy in cases of hepatic cirrhosis. Trials showed clinical improvements, but hardly any statistically significant improvements in liver function test [ 19 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…S-Adenosylmethionine, polyenylphosphatidylcholine, betaine, and antioxidants like vitamins A, C, E, B6, and B12 as well as branched chain amino acids are examples of substances studied for their potential efficacy in cases of hepatic cirrhosis. Trials showed clinical improvements, but hardly any statistically significant improvements in liver function test [ 19 29 ].…”
Section: Introductionmentioning
confidence: 99%